2022
DOI: 10.1021/acscatal.2c03871
|View full text |Cite
|
Sign up to set email alerts
|

Substituting Chromium in Iron-Based Catalysts for the High-Temperature Water–Gas Shift Reaction

Abstract: A set of doped iron oxides (chromium, aluminum, gallium, indium, manganese, zinc, niobium) were prepared by a one-step coprecipitation/calcination approach evaluated for their WGS activity under industrially relevant conditions and characterized in detail. The WGS activity after ageing the doped catalyst for 4 days at 25 bar follows the order chromium ≈ aluminum > gallium > indium > manganese > zinc > niobium for copper-codoped catalysts. The activated catalysts predominantly consist of magnetite, irrespective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Among all the dopants (Cr, Al, Ga, In, Mn, Zn, and Nb) tested, Al is also identified as the most promising one for substituting Cr in commercial applications. 12 Although plenty of knowledge has been attained, most of the previous studies focused on the establishment of a structure−activity relationship based on the fresh (simplified as f-) precursor, which is hematite (α-Fe 2 O 3 ), whereas the dynamic transformation of Al and its resultant spatial distribution within magnetite (the active site) is yet to be understood. In principle, a prereduction of hematite in a reducing environment (e.g., H 2 ) could induce the formation of oxygen vacancy on the surface, which in turn promotes the inward diffusion of the reduced Fe 2+ and the outward diffusion of bulk oxygen and cations (e.g., Al 3+ ) with a strong oxophilicity toward the surface, thereby stabilizing and reconstructing the surface structure as well.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all the dopants (Cr, Al, Ga, In, Mn, Zn, and Nb) tested, Al is also identified as the most promising one for substituting Cr in commercial applications. 12 Although plenty of knowledge has been attained, most of the previous studies focused on the establishment of a structure−activity relationship based on the fresh (simplified as f-) precursor, which is hematite (α-Fe 2 O 3 ), whereas the dynamic transformation of Al and its resultant spatial distribution within magnetite (the active site) is yet to be understood. In principle, a prereduction of hematite in a reducing environment (e.g., H 2 ) could induce the formation of oxygen vacancy on the surface, which in turn promotes the inward diffusion of the reduced Fe 2+ and the outward diffusion of bulk oxygen and cations (e.g., Al 3+ ) with a strong oxophilicity toward the surface, thereby stabilizing and reconstructing the surface structure as well.…”
Section: ■ Introductionmentioning
confidence: 99%
“…More recently, by comparing a series of doped Fe 2 O 3 with 5.3 wt % of Al 2 O 3 (2.81 wt % of Al), it was found that the Al substitute occupies both tetrahedral and octahedral sites in the bulk Fe 3 O 4 , resulting in a comparable activity and stability as Cr-doped iron oxide catalyst. Among all the dopants (Cr, Al, Ga, In, Mn, Zn, and Nb) tested, Al is also identified as the most promising one for substituting Cr in commercial applications . Although plenty of knowledge has been attained, most of the previous studies focused on the establishment of a structure–activity relationship based on the fresh (simplified as f-) precursor, which is hematite (α-Fe 2 O 3 ), whereas the dynamic transformation of Al and its resultant spatial distribution within magnetite (the active site) is yet to be understood.…”
Section: Introductionmentioning
confidence: 99%